It’s giving halal: Gen Z behavior bridging halal certification and MSMEs’ purchase intention - Arumbinang, Nimas Ayu; Saifuloh, Nur Imam (Center for Islamic Economics and Development Studies [P3EI], 2025)
Purpose – This study evaluates the influence of halal certification and Islamic marketing strategies on the purchase intention of MSMEs culinary products, with Gen Z consumer behavior as a mediating variable. The Islamic marketing approach references the SGIE 2023 Halal Lifestyle Marketing Mix (HLMM), which integrates the principles of amanah, taqwa, ihsan, and adl into the 4Ps framework. Methodology – Primary data were collected from Muslim respondents aged 17–26 years in West Java, a province promoting halal tourism and MSMEs growth. Structural Equation Modeling (SEM) was employed to test the proposed model.Findings – Halal certification significantly enhances consumer behavior, which in turn drives purchase intention. However, a negative direct effect of halal certification on purchase intention suggests a full mediation effect, where halal certification for MSMEs boosts Gen Z purchase intention only when it shapes how they think and act. Islamic marketing strategies also show a positive, albeit smaller, effect on consumer behavior and purchase intention. Implications – Government efforts focusing solely on MSME certification could trigger consumer skepticism and discourage purchases. Therefore, initiatives must be coupled with Islamic marketing strategies that translate halal labels into meaningful consumer value.Originality – This study advances the Theory of Planned Behavior (TPB) by modeling consumer behavior as a second-order construct and operationalizing Islamic marketing through the Halal Lifestyle Marketing Mix (HLMM). Focusing on MSMEs offers a novel perspective on how enterprises with typically weak brand identities can leverage the halal label as a market signal that shapes consumer intention.